Environmental adjudication - Lees, Emma; Pedersen, Ole W. (Oxford, UK ; Hart Publishing, Bloomsbury Publishing Plc, 2020)
"This book provides a detailed study of the role of the judiciary in environmental law. It examines theoretical issues concerning the role of judges in such decision-making, taking account of different legal cultures and contexts, exploring the multifaceted pressures which rest on the shoulders of courts when navigating the tensions between maintaining neutrality, resolving disputes, and providing guidance and assistance for future courts, policy-makers and decision-makers. In addition, it explores the particular challenges which arise in an environmental context, before articulating the range of environmental dispute 'models' which can and do exist in the context of the environmental law of England and Wales. The second part of the book looks at the consequences of these findings, and explores the relationship between adjudication and coherence before concluding with an exploration of what constitutes "good" environmental adjudication"--
Defining adjudication : nature and challenges -- Multidimensional environmental adjudication -- Avenues of environmental law adjudication -- Avenues of adjudication as power-broker -- Avenues as frames of reasoning -- Avenues as remedy determining -- The bricolage of environmental adjudication.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on online resource; title from digital title page (viewed on October 15, 2020).
Keywords: Environmental law; Political questions and judicial power; Environment law; Electronic books